The Transformation of the Conjugal Power Base: Yemeni Jewish Couples in an Israeli Town - Gilad, Lisa (Anthropologica, 2022)
This essay analyzes changes in the conjugal relationships of Yemeni Jewish immigrants from the time of their migration from pre-industrial Yemen to their entrenchment in contemporary Israel. Feminist writers often contend that under industrialized capitalism, the "domestic" domain becomes both "private" and the dominion of women, while the "politico-jural" domain becomes "public" and excludes women. The opposite happens to women in this study. In Israel, Yemeni Jewish women have achieved a public life for themselves in many areas, including paid labor, community activities, adult education, and so on. Their participation in extra-domestic activities has enabled them to gain more power and authority in the home than was experienced by women in Yemen. It is also argued that the place of immigrant women in Israeli society cannot be analyzed without understanding the experiences of their spouses in the economic domain of the wider society.